Update Breast Cancer 2019 Part 5 - Diagnostic and Therapeutic Challenges of New, Personalised Therapies in Patients with Advanced Breast Cancer. - Welslau, Manfred; Hartkopf, Andreas D.; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Lueftner, Diana; Belleville, Erik; Schuetz, Florian; Fasching, Peter; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Significant advancements have been made in recent years in advanced breast cancer and nearly all of them have been in the field of targeted therapy. Pertuzumab and trastuzumab-emtansine (T-DM1) have been able to be introduced in HER2-positive breast cancer. Now other anti-HER2 therapies are being developed (e.g. margetuximab, DS-8201a, pyrotinib) which can overcome other resistance mechanisms in the HER2 signalling pathway. In the field of hormone-receptor-positive breast cancer, an mTOR inhibitor and CDK4/6 inhibitors were introduced in the past. Now the introduction of the first PI3K inhibitor is forthcoming and this inhibitor will involve genetic testing of the tumour for a mutation in the PIK3CA gene. There are also significant advancements in triple-negative breast cancer: By combining chemotherapy and immunotherapy, an advantage for overall survival was able to be demonstrated in a subgroup (immune cells PD-L1-positive). The PARP inhibitor therapy for HER2-negative patients with a germ line mutation in BRCA1 or BRCA2 was also associated with an improved overall survival in a subgroup. These promising new study results are summarised in this review.
EVALuna2:206462